Unemployment and access to health care - Ilić, Boris; Ledinski Fičko, Sanja; Hošnjak, Ana Marija; Kovačević, Irena; Smrekar, Martina; Sedić, Biserka (2019)
Introduction. At the time of the global economies’ recovery from the effects of fourth major recession after the Second World War, there was a major increase in the unemployment rate that created a significant existential and public health challenge Aim. The aim of this study was to provide a systematic review of available research on effects of unemployment on access to health care, and consequentially on health of the population. Methods. A systematic search of relevant, peer-reviewed electronic databases was conducted to identify systematic reviews, review articles, original research papers and reports for the period of past ten years. Results. 10.234 results were initially identified, five of which were included in this review. Conclusion. Significant number of studies confirms that the unemployed individuals, due to sometimes limited access to health care, have impaired health in comparison to the employed population, both in physical and mental health. Global economic change will have a stronger impact on the health of the population in poor countries, therefore a fair and comprehensive system of health care for the unemployed is of paramount importance for the purpose of preserving the health of the population.
Uvod. U trenutku oporavka globalne ekonomije od posljedica četvrte velike recesije nakon Drugog svjetskog rata, koja se javila završetkom prve dekade 21. stoljeća – stopa nezaposlenosti posljedično je visoka te predstavlja znatan egzistencijalni i javnozdravstveni izazov. Cilj. Pružiti sistematični pregled dostupnih istraživanja o utjecaju nezaposlenosti na pristup zdravstvenoj zaštiti, kao i o posljedičnom utjecaju na samo zdravlje pojedinca. Metode. Provedena je sistematična pretraga elektroničkih znanstvenih baza za sistematične preglede, pregledne članke, originalne istraživačke radove te izvješća u periodu od posljednjih deset godina. Rezultati. Sistematičnom pretragom recenziranih baza podataka pronađeno je ukupno 10 234 članaka, od kojih je pet uključeno u ovaj pregled. Zaključak. Znatan broj studija dokazuje da su nezaposlene osobe, uslijed ograničenog pristupa zdravstvenoj zaštiti, narušenijeg zdravlja od zaposlenih, kako s fizičkog tako i psihičkog aspekta, što je posljedica negativnih učinaka koje sa sobom nosi gubitak zaposlenja. Globalne ekonomske promjene imat će snažniji utjecaj na zdravlje populacije u siromašnim državama nego u bogatima, stoga je pravedan i sveobuhvatan sustav zdravstvene skrbi za nezaposlene od iznimne važnosti u svrhu očuvanja zdravlja populacije.
Bibliografija: 20 jed.
Abstract ; Sažetak.
Keywords: Zdravstvena zaštita -- Nezaposlenost -- Ekonomska kriza -- Recesija